Digital Transformation as Revitalization of Work Culture in Good Institutional Governance at FITK Walisongo Semarang, Indonesia and Southern Thailand (Pascasarjana IAIN Kudus, 2025)
This study aims to analyze the role of digital transformation acceleration in revitalizing work culture to support good institutional governance at the Faculty of Tarbiyah and Teacher Training (FITK) at UIN Walisongo, Indonesia, and Ma’had Darul Ma’arif Al Fathani, Thailand. Digital transformation encompasses the application of technology and contributing to transparent, accountable, and efficient institutional governance. This study employs a qualitative approach with a comparative study method. Data were collected through in-depth interviews with leaders, educators, and administrative staff at both institutions, as well as through participant observations. Thematic techniques and a grounded theory approach were used to analyze the data and understand the dynamics of digital transformation and work culture at both institutions. The results show that FITK Walisongo’s digital transformation is supported by national policies that increase work efficiency and internal collaboration. In contrast, Ma’had Darul Ma’arif faces infrastructure constraints and resistance; however, ongoing training has begun to strengthen staff engagement and institutional openness. In conclusion, accelerating digital transformation plays a strategic role in strengthening work culture and promoting good governance values in educational institutions worldwide.